Specific Serological Relationships Among Partially Purified DNA Polymerases of Avian Leukosis-Sarcoma Viruses, Reticuloendotheliosis Viruses, and Avian Cells - Mizutani, Satoshi (1974)
Specific serological relationships were found among the partially purified DNA polymerases of the two groups of avian viruses whose virions contain RNA and a DNA polymerase—the avian leukosis-sarcoma viruses and the reticuloendotheliosis viruses—and three avian species which are natural hosts for these viruses: chickens, turkeys, and Pekin ducks. No relationships were found to DNA polymerases of HeLa cells or Escherichia coli. These results are consistent with the hypothesis that RNA viruses with a DNA polymerase originated from normal cellular components.